Dyonic integrable models - Gomes, J. F. [UNESP]; Gueuvoghlanian, E. P. [UNESP]; Sotkov, G. M. [UNESP]; Zimerman, A. H. [UNESP] (Elsevier, 2001)
A class of non-abelian affine Toda models arising from the axial gauged two-loop WZW model is presented. Their zero curvature representation is constructed in terms of a graded Kac-Moody algebra. It is shown that the discrete multivacua structure of the potential together with non-abelian nature of the zero grade subalgebra allows soliton solutions with non-trivial electric and topological charges. The dressing transformation is employed to explicitly construct one and two soliton solutions and their bound states in terms of the tau functions. A discussion of the classical spectra of such solutions and the time delays are given in detail. © 2001 Elsevier Science B.V.